Immunological treatment of liver tumors - Chiriva-Internati, Maurizio (World J Gastroenterol, 2005)
Although multiple options for the treatment of liver tumors have often been described in the past, including liver resection, radiofrequency ablation with or without hepatic pump insertion, laparoscopic liver resection and the use of chemotherapy, the potential of immunotherapy and gene manipulation is still largely unexplored. Immunological therapy by gene manipulation is based on the interaction between virus-based gene delivery systems and dendritic cells. Using viruses as vectors, it is possible to transduce dendritic cells with genes encoding tumor-associated antigens, thus inducing strong humoral and cellular immunity against the antigens themselves. Both chemotherapy and radiation therapy have the disadvantage of destroying healthy cells, thus causing severe side-effects. We need more precisely targeted therapies capable of killing cancer cells while sparing healthy cells. Our goal is to establish a new treatment for solid liver tumors based on the concept of cytoreduction, and propose an innovative algorithm.